AB1294 Impact of work status on health-related quality of life (HRQOL) in ra. (12th June 2018) - Alemao, E.; Boonen, A.; Guo, Z.; Iannaccone, C.; Frits, M.; Weinblatt, M.E.; Shadick, N.A.
Abstract : Background: Compared to the general population, RA patients (pts) are less likely to be employed and have lower HRQoL. 1, 2 However, data on impact of work status on HRQoL in RA pts are limited. Objectives: Evaluate association between work status and HRQoL in RA pts. Methods: We analysed data from adult pts enrolled in a large sequential RA registry. Physicians assessed pt demographics, clinical characteristics, disease activity and laboratory parameters at baseline (BL) and then annually. Follow-up questionnaires to assess pt-reported outcomes were administered every 6 months and included HRQoL measures (12-Item Short-Form Health Survey physical and mental component summary [SF-12 PCS, MCS], EuroQoL-5 Dimension [EQ-5D]) and work status; higher score indicates better health for all 3 HRQoL measures. General linear mixed models with repeated measures were used for SF-12 analysis and finite mixture models for the EQ-5D analysis, controlling for BL covariates. Results: A total of 974 RA pts with HRQoL information were included: 49.3% (n=480) 'employed for pay', 38.9% (n=379) 'employed not for pay' (retired, homemaker or student), 11.8% (n=115) 'not employed or on disability'. Pts employed for pay were younger and had lower disease activity compared with other groups (table 1). Compared with pts 'not employed or on disability', pts employed had significantly higher PCS (mean [SE] 7.17 [0.82]; p<0.001), MCS (5.39 [0.80]; p<0.001) and EQ-5D (0.48 [0.16]; p=0.0031) scores. Similar results were observed comparing pts 'employed not for pay' to pts 'not employed or on disability' (Table 2). Conclusions: Work status and household income in RA are independently associated with HRQoL. More studies are needed to evaluate impact of work on changes in HRQoL in RA pts. References: [1] Uhlig T, et al. J Rheumatol2007;34:1241–7. [2] Chorus AM, et al. Ann Rheum Dis2003;62:1178–84. Disclosure of Interest: E. Alemao Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, A. Boonen: None declared, Z. Guo Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, C. Iannaccone: None declared, M. Frits: None declared, M. Weinblatt Grant/research support from: Amgen, Bristol-Myers Squibb, Crescendo Bioscience, Sanofi, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Crescendo Bioscience, Lilly, Merck, Novartis, Pfizer, Roche, Samsung, N. Shadick Grant/research support from: Amgen, BRASS registry, Bristol-Myers Squibb, Mallinckrodt, Consultant for: Bristol-Myers Squibb